Практика як складова підготовки майбутніх економістів до професійної діяльності - Кліпа, Юлія (My University, 2017)
У статті розкрито особливості підготовки майбутніх економістів до професійної діяльності та умови організації їх практичної підготовки. Доводиться, що практична підготовка майбутніх економістів є вагомою складовою навчального процесу. Практика залишається широким полем перевірки теоретичних знань, накопичених студентами у ВНЗ та становить собою підґрунтя для поглибленого засвоєння проблем, що мають місце у відповідній сфері. Охарактеризовано складові формування конкурентоспроможного фахівця на ринку праці. Під час проходження виробничої практики студент має можливість перевірити свій професіоналізм, вивчити реальні ситуації; перевірити знання, отримані під час навчання; самостійно приймати рішення, обґрунтовуючи їх доцільність перед керівником практики. Майбутній фахівець навчається субординації, роботі в колективі, отримує навички професійного спілкування. The article reveals the aspects of future economists training for professional activities and the conditions for organizing their practical training. The future economists practical training is proved as an important component of the educational process. Practice remains a broad field for checking the theoretical knowledge accumulated by students in higher education institutions. It is also basis for a profound assimilation of problems that are taking place in the relevant field. The article proves that for the successful traineeship it is necessary to promote cooperation between teachers-heads of practice from higher educational institutions and heads of practice from operating department for making practice training programs and for carrying out work on scientific research. The components of a competitive specialist training in the labor-market are characterized. During the traineeship, the student has an opportunity to test his professionalism, to study real situations, to check the knowledge gained during training, to make decisions independently, justifying their expediency to the head of practice. The future specialist works in a team, learns subordination, gets skills of professional communication. In the article the author confirms that the organization of practical professional training of future specialists of economic specialties in higher educational institutions is carried out both in the study of professionally directed theoretical disciplines and in job training. Professional preparation is based on the training of highly professional and creative specialists capable of adapting to the modern requirements of the economy and the labor-market.
Keywords: професійна підготовка; професійна освіта; майбутній економіст; професійна діяльність; практична підготовка; професійна компетенція; виробнича практика